Nutritional evaluation of a protein concentrate from horse bean ceeds - ΚΑΛΑΪΣΑΚΗΣ Π.; ΠΑΠΑΔΟΠΟΥΛΟΣ Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The net utilization of a protein-cocentrate from horse bean seeds was determined in growing chicks and it was found to be 44.4%, after addition with methionine 52% and after addition with methionine and lysine 57.2%. The incorporation of the protein-concentrate into the normal ration of the fattening chicks showed that the protein-concentrate replaced successfully the soya bean meal.